EZH2 inhibition promotes ANGPTL4/CREB1 to suppress the progression of ulcerative colitis - Li, Kun; Yang, Jing; Lei, Xiao-Fei; Li, Shuang-Ling; Yang, Hong-Li; Xu, Chang-Qing; Deng, Li (Life sciences (1973), 2020)
Enhancer of zeste homolog 2 (EZH2) is associated with ulcerative colitis development. However, the mechanism of EZH2 in ulcerative colitis progression remains unclear. Lipopolysaccharide (LPS)-treated Caco-2 cells and dextran sodium sulfate (DSS)-treated mice were used as model of ulcerative colitis. The levels of EZH2, angiopoietin-like 4 (ANGPTL4) and cyclic adenosine monophosphate response element-binding protein 1 (CREB1) were tested via quantitative real-time polymerase chain reaction (qRT-PCR) and western blot. Cell viability and apoptosis was measured via 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-tetrazolium bromide or flow cytometry. The abundances of inflammatory cytokines were examined via qRT-PCR and enzyme-linked immunosorbent assay. The association between EZH2 and ANGPTL4 was explored via chromatin immunoprecipitation. The colon damage in DSS-treated mice was investigated by colon length, histological analysis, inflammatory response and apoptosis. LPS induced viability inhibition, inflammatory response and apoptosis in Caco-2 cells. EZH2 expression was increased but ANGPTL4 and CREB1 levels were decreased in LPS-challenged Caco-2 cells. Overexpression of ANGPTL4 or CREB1 suppressed LPS-induced damage in Caco-2 cells. EZH2 could target ANGPTL4 to mediate CREB1 expression. Inhibition of EZH2 suppressed LPS-caused injury. Moreover, knockdown of ANNGPTL4 or CREB1 attenuated the role of EZH2 inhibition. DSS caused the reduced colon length and increased inflammatory response as well as apoptosis. EZH2 expression was up-regulated but ANGPTL4 and CREB1 expression were down-regulated in DSS-treated mice. Inhibition of EZH2 declined LPS-induced injury in Caco-2 cells by mediating ANGPTL4 and CREB1, indicating the potential of EZH2 in treatment of ulcerative colitis.